The Need for Cognition on Earthquake Risk in China Based on Psychological Distance Theory. (31st December 2020) - Li, Shasha; Zhai, Guofang; Fan, Chenjing; Chen, Jing; Li, Li
Abstract : There is a high need for cognition on earthquake risk to improve the public's risk knowledge and risk awareness, so that they can make right decisions and take quick actions regarding mitigation measures and adjustments. In this study, search engine query data from the Baidu Index were extracted to reveal the information search behaviors of the Chinese public regarding the earthquake risk from 2010 to 2012. The data were also analyzed to discuss the characteristics of need for cognition on a nationwide scale and over the long term. The results showed that (1) graphic representations of need for cognition adhere to a "half-peak pattern" before and after earthquake events and (2) dimensions in psychological distance theory, such as temporal distance (time span between earthquakes), spatial distance, and social distance (geographic location) influence the need for cognition on earthquake risk that was the time and spatial discount effect. The implications for theory and practice regarding risk communication and management are discussed and concluded.